2022
DOI: 10.1101/2022.03.14.484124
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prediction of m6A and m5C at single-molecule resolution reveals a cooccurrence of RNA modifications across the transcriptome

Abstract: The expanding field of epitranscriptomics might rival the epigenome in the diversity of the biological processes impacted. However, the identification of modifications in individual RNA molecules remains challenging. We present CHEUI, a new method that detects N6-methyladenosine (m6A) and 5-methylcytidine (m5C) at single-nucleotide and single-molecule resolution from Nanopore signals. CHEUI predicts methylation in Nanopore reads and transcriptomic sites in a single condition, and differential m6A and m5C methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 87 publications
(235 reference statements)
1
26
0
Order By: Relevance
“…We should note that all artificial mixes representing distinct RNA modification stoichiometries contained the same number of reads (n=1000), to ensure that coverage would not be a confounder in the analysis. Our results revealed that stoichiometry had a major effect in the detection of RNA modifications (Figure 2D), in agreement with previous works 57,59 . Notably, we observed that the effect of stoichiometry was strongly dependent on the RNA modification type.…”
Section: Performance Of Nanopore-based Rna Modification Detection Alg...supporting
confidence: 93%
See 1 more Smart Citation
“…We should note that all artificial mixes representing distinct RNA modification stoichiometries contained the same number of reads (n=1000), to ensure that coverage would not be a confounder in the analysis. Our results revealed that stoichiometry had a major effect in the detection of RNA modifications (Figure 2D), in agreement with previous works 57,59 . Notably, we observed that the effect of stoichiometry was strongly dependent on the RNA modification type.…”
Section: Performance Of Nanopore-based Rna Modification Detection Alg...supporting
confidence: 93%
“…RNA modifications can then be identified using two main approaches: (i) in the form of systematic base-calling 'errors' [47][48][49][50][51] , or (ii) in the form of alterations in the current signal (i.e., altered current intensities, dwell times and/or trace) 43,[52][53][54][55][56][57] . In recent years, a plethora of algorithms to detect RNA modifications in DRS datasets have been developed 47,53,[56][57][58][59] ; however, the overlap between predicted RNA modified sites by different algorithms is poor 49,57 , limiting our ability to extract meaningful biological conclusions from these datasets. Moreover, it is currently unclear how the performance of each algorithm varies depending on the RNA modification type, modification stoichiometry and sequencing depth, thus limiting the applicability of DRS for the detection of dynamically regulated RNA modifications in biological contexts 45 .…”
Section: Introductionmentioning
confidence: 99%
“…Information obtained from full-length native RNA nanopore sequencing has been used to detect isoform-specific modifications (Aw et al 2021), as well as to predict RNA modifications in individual reads (Begik et al 2021;Acera Mateos et al 2022), providing a resolution of the epitranscriptome at an unprecedented level, which had not been obtained using short-read sequencing data (Leger et al 2021). With the help of computational tools, unmodified and modified reads can be distinctly classified based on their unique current signal signatures, making it possible to detect even slight changes in the proportion of modified molecules, referred to as modification stoichiometry, across different conditions and cell types (Begik et al 2021;Pratanwanich et al 2021).…”
Section: Main Textmentioning
confidence: 99%
“…RATTLE modularity, with the ability to parameterize each step, means it can be easily adapted to any sample type. Additionally, RATTLE rich output, including information about the predicted transcripts and genes, as well as the reads used to build each transcript, will prove valuable in downstream analyses, including the study of differential transcript usage [25], the analysis of single-cell long-read sequencing [26], and the identification of RNA modifications in non-model species [27]. RATTLE lays the foundation of exciting developments in long-read transcriptomics.…”
Section: Discussionmentioning
confidence: 99%